The Grass Roots Curriculum Model in Basic Education through Self-Development Programs - Atin, Sri; Rokhimawan, Mohamad Agung (Jurnal Ilmiah Sekolah Dasar, 2024)
The self-development program that is implemented in madrasas is motivated by various moral and ethical issues: such as bullying, fights, lack of manners, and even criminal acts that are rife today. This study aims to analyze the implementation the curriculum model grassroots through self-development programs in madrasas. This study uses a descriptive qualitative research method with a phenomenological approach with a case study type. To obtain research data, researchers used non-participant observation techniques, structured interviews, and documentation. The data sources in this study were the head of the madrasah, the deputy head of curriculum, and teachers. The data selection technique uses a purposive sampling technique. This research's data analysis technique uses triangulation of data sources. The results of the research findings indicate that the self-development program is carried out in madrasas in stages: (1) bullying and lack of manners are identified; (2) Madrasas review the programs that have been implemented; (3) Madrasas propose various types of programs; (4) Self-development programs at madrasah ibtidaiyah can overcome bullying and lack of manners; (5) The self-development program has been well implemented including programs this tahfid camp, Ramadan Ceria, Qoilulah, Rihlah, Outschool, Tasmi' Parade, Pioneer Class, and Home Visit. The grassroots curriculum model has been well implemented through self-development programs in madrasas. In the future, a more accurate and measurable evaluation of the implemented self-development program will be carried out.